Differences in the Results of Determining Glucose Levels using the Poct Device on Specimens Taken when the Finger is Dry and on Fingers that are Still Wet with 70% Alcohol Cotton - Annisa , Nur; Arwie, Dzikra; Aryandi, Rahmat (Frontiers in Sustainable Science and Technology, 2024)
Blood glucose is a sugar found in the blood that is formed from Carbohydrates in food that are absorbed in large quantities into the blood and converted in the heart. In blood sampling alcohol is used to clean and disinfect the skin area before injection. This helps reduce the risk of infection by killing germs on the skin's surface. This study aims to determine the differences in the results of glucose level determination using the POCT device on specimens taken when the finger is dry and when the finger is still wet with 70% alcohol cotton. This study uses a laboratory experimental research design. The population of this study were students of Stikes Pantita Husada Bulukumba and the sample of this study was 53 capillary blood samples. The results of this study indicate that there is a significant difference in glucose levels in specimens taken when the fingers were dry and those that were still wet with 70% alcohol cotton. The results of the statistical test show that each data is normally distributed which meets the requirements for conducting the Wilcoxon test. The final results show a p-value of 0.000 <0.05, meaning that there is a significant difference in the average or a significant difference in specimens taken when the fingers were dry and those that were still wet. Conclusion: Based on the research conducted, it can be concluded that there is a difference in glucose levels between specimens taken when the fingers were dry and those that were still wet.